Involving HRM Indicators on Firm Financial Performance: Correlation Study Between Social Factors, Work Environment, and Job Satisfaction - Lukman S (Pusat Penerbitan dan Publikasi Ilmiah, FEB, Universitas Muslim Indonesia, 2023)
The purpose of this paper is to explore the relationship between factors such as job satisfaction, social factors, and work environment, and their impact on an organization's financial performance. This paper is based on a review of existing literature on the relationship between employee happiness and satisfaction and financial performance. Various theories, such as Expectancy Theory, Locke and Latham's Job Satisfaction Theory, and Fredrick Herzberg's Job Satisfaction Theory, are used to support our findings and analyze based quantitative with SMART-PLS to answer the hypothesis. The study results show that Job satisfaction has a positive impact on financial performance. Increased job satisfaction can reduce employee turnover, increase productivity, and reduce recruitment and training costs. Social factors, such as a positive organizational culture, effective communication, social support, and team diversity, also affect financial performance by creating a more dedicated and motivated workforce. Social factors also have a positive and significant effect on job satisfaction. Positive relationships with coworkers and superiors, good communication, and social support contribute to higher job satisfaction. A good work environment, including a comfortable physical environment, a positive work atmosphere, healthy employee relations, supportive company policies, and a positive work culture, contributes to employee motivation and company performance. This paper highlights the importance of factors related to employee happiness and satisfaction in achieving better financial performance. It provides managers with insights on how to improve employee satisfaction, build a positive organizational culture, improve communication, and create a supportive work environment. The findings also contribute to the existing organizational and management theories by emphasizing the significance of psychological and social factors in predicting financial performance.